2018
DOI: 10.2174/18744478018120100128
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Truck At-Fault Crashes Using Crash and Traffic Offence Data

Abstract: Introduction:The number of truck-related injuries and deaths can be reduced by understanding the factors that contribute to the higher risk of truck-related crashes and violations. Truck drivers are at fault of more than 80% of all the truck crashes on Wyoming interstates, and the literature review indicated that in order to identify appropriate countermeasure to crashes, each crash type should be analyzed individually. The literature review also revealed that relationships exist between driving records and dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…e results show that there is a significant relationship between driving experience and driving offenses such as speeding and not fastening seat belts [2, 3, 5, 9, 18-20, 23, 24]. Other studies in this field have found that violations such as long-distance disobedience [9,24], seat belts [2,5], technical defect [5,23], alcohol abuse [3,5], and factors such as accident's history [2,5,24], violations records [25,26], and some parameters of Driving Behavior Questionnaire (DBQ) [18,19,24] have a significant impact on the occurrence of cargo fleet accidents.…”
Section: Literature Reviewmentioning
confidence: 96%
“…e results show that there is a significant relationship between driving experience and driving offenses such as speeding and not fastening seat belts [2, 3, 5, 9, 18-20, 23, 24]. Other studies in this field have found that violations such as long-distance disobedience [9,24], seat belts [2,5], technical defect [5,23], alcohol abuse [3,5], and factors such as accident's history [2,5,24], violations records [25,26], and some parameters of Driving Behavior Questionnaire (DBQ) [18,19,24] have a significant impact on the occurrence of cargo fleet accidents.…”
Section: Literature Reviewmentioning
confidence: 96%
“…One of the most important offenses identified in past studies as a major contributing factor to the occurrence of accidents is speeding [9-11, 13-15, 21-23]. Other studies in this field have found that offenses such as maintaining safe distance to front vehicle [21,23], fastening seat belt [14,22], technical defect [13,22], alcohol abuse [15,22], and other related factors such as a history of a crash [14,21,22], a history of misconduct [24][25][26], and some parameters of the Driving Behavior Questionnaire [9,11,21] have a significant impact on the occurrence of accidents for commercial fleets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some other studies also investigated different geometrical factors that contribute to truck-related crashes (16,17), with similar findings on the contributions of traffic and roadway features. Some recent studies in Wyoming investigated truckrelated crashes along Interstate highways using traffic violation and crash data (18)(19)(20). Those studies employed two approaches to identify factors contributing to truckrelated crashes and truck-related violations using the logistic regression method.…”
Section: Literature Reviewmentioning
confidence: 99%